Contribution of early season cowpea to late season maize in the savanna zone of West Africa - Carsky, R.J.; Singh, B.B.; Oyewole, B. (Informa UK Limited, 2001)
In the moist savanna zone with a 180 to 190 day growing period, early season cowpea immediately followed by a late season cereal crop can maximize the benefit of the legume to the cereal. Traditional cereal crops for this system are millet and sorghum but new early maize varieties can also be used. A study was conducted to estimate the contribution of the early season cowpea to late season maize during three years on two fields in central Kaduna State in northern Nigeria. Without insecticide application, early season cowpea grain yield averaged almost 500 kg ha−1 over all environments including a site where P deficiency was corrected in the second year. N content of cowpea residues after grain harvest averaged approximately 15 and 30 kg ha−1 at the low-P and moderate-P sites, respectively. Mean maize grain yield without urea or previous cowpea (290 kg ha−1 in five environments) was increased to 760 kg ha−1 with urea application (30 and 60 kg ha−1 treatments combined) and 690 kg ha−1 after early season cowpea (three varieties combined). Maize grain yield after early season cowpea without N application to maize was maintained at levels higher (at p < 0.06) than 30 kg N ha−1 as fertilizer. Thus, cowpea cultivation in the early season appears to be an effective indigenous solution for supplying a small amount of N for cereal production. The study showed the importance of adequate P availability for the rotation system to succeed.